Development of Interactive Digital Flipbook Learning Media Assisted by Augmented Reality to Improve Concept Understanding in Science Subjects at Elementary School - Indah Nurkomalasari; Atikah Syamsi; Misbah Binasdevi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to develop and test the feasibility and effectiveness of digital flipbook learning media assisted by Augmented Reality (AR) on the five senses material in Natural Sciences (IPA) learning for fifth grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 37 fifth-grade students at SDN Kumbung I. The research instruments included validation sheets from media experts, language experts, and subject matter experts, student response questionnaires, and science concept comprehension tests. The validation and student response data were analyzed using percentage techniques, while the concept comprehension data were analyzed using N-Gain Score. The results showed that the AR-assisted digital flipbook media had a very high feasibility level based on the assessments of media and language experts at 95% and subject matter experts at 100%. Student responses to the use of the media also showed a very feasible category with a percentage of 86.95%, indicating that the media was interesting, easy to use, and helped with understanding the material. The effectiveness test showed an N-Gain value of 0.7525 in the high category, indicating a significant increase in students' science concept comprehension after using the media. Thus, AR-assisted digital flipbook media is declared feasible and effective for use as an alternative science learning medium for sensory material in elementary schools.